Ehrlichia and Anaplasma - Yuexun Tian; Cynthia C Lord; Eva A. Buckner (EDIS)
Ehrlichia and Anaplasma are bacteria that cause diseases, known as ehrlichiosis and anaplasmosis, in humans and other animals. Ehrlichia and Anaplasma are primarily transmitted through the bites of infected hard ticks, such as the lone star tick, the blacklegged tick, and the American dog tick. This publication describes the various forms of ehrlichiosis and anaplasmosis and the tick vectors.